KHR. AS'AD SYAMSUL ARIFIN'S DA'WAH STRATEGY IN CONQUERING THE RASCALS IN SITUBONDO DISTRICT - fikri riswandha cahya (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2024)
This article examines KHR's Da'wah Strategy. As'ad Syamsul Arifin in Conquering Rogues in Situbondo Regency. As in general,